Procedures in marriage and family therapy - Brock, Gregory W. (Allyn and Bacon, 1999)
Provides practical information about how to carry out the important procedures in marriage and family therapy. This book serves as a student's or clinician's "handbook," with explanations of how to handle a range of situations encountered in everyday family practice. It includes topics, such as limiting risk, out-of-session work, and more.